A Review of the Study "Measurement and Analysis of Corruption Using Objective Data" by T. V. Natkhov and L. I. Polischuk - Ivan Aymaliev (Journal of Economic Sociology, 2015)
The purchase of “beautiful” car registration plates from state authorities is legal in many developed democracies. However, in Russia this practice is strictly prohibited. Anecdotal evidences suggest that Russians circumvent the law by bribery or blat. Given the ambiguous nature of informal payments to public officials, Natkhov and Polischuk propose a new objective measure of corruption based on the distribution of “beautiful” registration numbers. This article reviews their study and its discussion at the Sociology of Markets seminar at the Higher School of Economics. The authors hypothesize that in the absence of corruption, the “beautiful” registration numbers will be distributed normally regardless of automobile brands. In the presence of corruption, however, the “beautiful” registration numbers will be concentrated across luxury brands. They argue that a higher than usual concentration of “beautiful” registration numbers is an indicator of corruption. To test this hypothesis, they draw upon corruption economics theories and use an innovative dataset that includes car brands and registration numbers issued by the police in the city of Moscow from 2000–2007, as well as a 2014 quantitative survey with citizens (N = 1,552). The economists find that the “beautiful” registration numbers are concentrated across luxury car brands, but are normally distributed across ordinary brands. They conclude that the higher than usual concentration of “cherish” registration numbers among luxury brands is an indicator of higher police corruption. Nevertheless, sociologists suggest that the proposed index is rather an indicator of social status, personal connections or elite consumption preferences.